Explaining key stakeholders’ preferences for potential policies governing psychiatric electroceutical intervention use - Aaron M. McCright; Eric D. Achtyes; Robyn Bluhm; Laura Y. Cabrera (npj Mental Health Research)
Abstract In recent years, legislators in many states have proposed laws governing the use of psychiatric electroceutical interventions (PEIs), which use electrical or magnetic stimulation to treat mental disorders. To examine how the PEI views of relevant stakeholder groups (e.g., psychiatrists, patients, caregivers, and general public) relate to preferences for proposed policies governing PEI use, we analyze data from a survey on using one of four PEIs to treat major depressive disorder administered to national samples of the stakeholder groups above. We find that the three non-clinician groups’ similar PEI policy preferences differ significantly from those of psychiatrists—with the greatest divide on policies governing the use of electroconvulsive therapy. This divide between psychiatrists’ and non-clinicians’ PEI policy preferences was greater with access-reducing than with access-expanding policies. We advise policymakers to consider such variation in the preferred availability of PEIs across modalities and stakeholder groups when crafting legislation on these interventions.